Testing, characterization and numerical prediction (uni-axial tension and bend test) of Double-side TIG welded SS321 plate for pressure vessel application. (June 2022) - Kumar, S. Mohan; Kannan, A. Rajesh; Pramod, R.; Shanmugam, N. Siva; Dhinakaran, V.
Abstract: This study reports the welding of SS321 nuclear grade stainless steel employed for pressure vessel industries using the novel Double-side tungsten inert gas (DS-TIG) welding. The optimization technique (Taguchi-based Grey relational analysis (GRA)) used in this research will give firsthand knowledge to the industry concerning the process variables to produce quality weldments using the DS-TIG welding method. The optimized combination of input variables was noted to produce a butt joint with SS321 plate having 6 mm thickness: Arc length ( Al ) 3 mm, Arc current ( I ) 220 Amps, and Traverse speed ( S ) 120 mm/min. The Analysis of variance (ANOVA) table was created to estimate the significance of the input process variables in the weldments. The impact of process variables on the Depth of penetration: DoP and Bead width: BW in relation to the heat input was evaluated. The microstructural features and mechanical integrity of the DS-TIG weldment made with the optimized combination of input process variables were analyzed utilizing Optical microscopy, Electron back scattered diffraction (EBSD), Tensile, Hardness, Impact, and Bend tests. A Finite element (FE) model of uni-axial tension and bend test was developed to predict the tension strength (base and weld metal) and stress distribution during bend test of DS-TIG specimen. A good agreement between the experimental and predicted results was noticed (error less than 5%) in terms of stress vs. strain plot (uni-axial tension) and load vs. displacement plot (bend test). Highlights: A novel DS-TIG welding process was used to weld SS321. TIG welding output responses of DoP and BW are measured. Tensile, Hardness, Bend, and Impact strength are evaluated. The microstructure is measured and analyzed using EBSD, which is new. FE analysis of the uni-axial tension and bend test was performed to predict their strength.